Dendrobium officinale Polysaccharide Protected CCl4-Induced Liver Fibrosis Through Intestinal Homeostasis and the LPS-TLR4-NF-κB Signaling Pathway - Wang, Kaiping; Yang, Xiawen; Wu, Zhijing; Wang, Hongjing; Li, Qiang; Mei, Hao; You, Ruxu; Zhang, Yu (Frontiers in Pharmacology, 2020)
We explored the therapeutic effects of Dendrobium officinale polysaccharides (DOP) on CCl4-induced liver fibrosis using the rat model from the aspect of intestinal and hepatic axis. Histopathological staining results showed that DOP alleviated extensive fibrous tissue proliferation in the liver interstitial and lessened intestinal mucosal damage. Western blot and PCR results showed that DOP maintained intestinal balance by up-regulating the expression of ZO-1, Occludin, Claudin-1 and Bcl-2 proteins while down-regulating the expression of Bax and caspase-3 proteins in the intestine. The TEER value of LPS-induced Caco-2 monolayer cell model was increased after administration of DOP. It illustrated that DOP can protected intestinal mucosal barrier function. DOP decreased LPS entry into the liver, and inhibited activation of the TLR4/ NF-κB signaling pathway. DOP reduced the expression of inflammatory factors TGF-β and TNF-α, increased the expression of anti-inflammatory factor IL-10, and significantly decreased α-SMA and collagen I expression. These indicated that DOP inhibited the activation of LPS-TLR4-NF-κB signaling pathway through strengthening tight junction between cells and reducing apoptosis to alleviate liver fibrosis.